Numerical study of LED-pumped Nd:KGW laser - Shermatova, Feruza; Payziyev, Shermakhamat; Sherniyozov, Anvarjon (Oficyna Wydawnicza Politechniki Wrocławskiej, 2024)
In this study, we conducted a numerical analysis of LED-pumped solid-state lasers. We developed a simulation model for LED-pumped Nd:KGW and Nd:YAG lasers, incorporating a “five-way” pumping module. The spectral and laser characteristics of Nd:KGW were analyzed. Our results indicate that Nd:KGW crystals may be more suitable for LED pumping compared to the widely used Nd:YAG, as evidenced by their comparative performance. LED pumped Nd:KGW laser showed higher slope efficiency. We provide estimates for the laser output and absorption distribution. The study explores the influence of Nd concentration levels within Nd:KGW on laser outputs when employing LED pumping, while also addressing thermal considerations in Nd:KGW rods.
Optica Applicata, Vol. 54, 2024, nr 3, s. 409-421
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; Nd:YAG; LED-pumped lasers; Nd:KGW; LEDs